MENGELOLA DAN MEMBIMBING ESPORT ORGS - Rostina Uduas; Melky Pangemanan (STIKES Columbia Asia Medan, 2025)
Esports organizations have rapidly grown into a highly competitive industry. Managing and guiding an esports organization requires a holistic approach, encompassing business, sports and technology aspects. This research aims to identify challenges and opportunities in managing esports organizations. Through literature reviews and case studies, this research will examine key elements such as team development, financial management, branding, and marketing strategy. Apart from that, this research will also discuss the importance of adapting to changes in the dynamic esports landscape.